Comment on “Governance ideas in Kong-Zi Jia Yu and their contemporary values” - Jiao, Xiaoxia (2023)
Reference of the commented article: LI, H. Governance ideas in Kong-Zi Jia Yua and their contemporary values. Trans/Form/Ação: Revista de Filosofia da Unesp, v. 47, n. 1, e0240003, 2024.